COMBATING THE NORMAL LIFE WITH SENSATIONAL INTERPRETATIONS: A STUDY ON THE PSYCHOLOGICAL TRAUMA OF THE MODERN WOMEN - Joy, Ancymol; R, Vasanthan (International Journal of Psychosocial Rehabilitation, 2020)
The social concepts of gender and sex and its influences on the psychological level of human being especially women is a topic of discussion in the contemporary critical theory. The psychological dilemma of women regarding their body and health encompasses various studies of women’s identity and the position of women. The inferior status of women physically, economically and politically and the consequences of this social condition influence the psychology of women. The societal factors which evaluate the psychological trauma of women in this modern society are questionable in the present culture. The gender issues and the socio-political conditions have an impact on the physical as well as the mental health of women. The biological aspects, domestic conditions, cultural reverberations and the image of women in the society directly regulate the psychological concerns of the world of women. In this way, this article mainly focuses on the psychological trauma of modern women in terms of their physical appearances and the biological nonconformity between men and women in the contemporary society.